Picturesque places of Ukraine as tourism-recreation - Astafieva, A. (ХДАК, 2024)
Going on vacation, we want to spend it interesting. For some it is enough to just sit at home and finally get some sleep, for some it is an excuse to travel and discover something new. Of course, there are many interesting places in the world, but there are more than enough of them in our country. The peaks of the Carpathian Mountains to the plains along the Black Sea are a treasure trove of history, culture and breathtaking landscape. Ukraine is more than just its size, it is a country painted with a palette of diverse geographical features, imagine hills covered with golden fields of wheat interspersed with deep mysterious forests, images of rocky mountain ranges, their peaks covered with snow, standing guard over the land , which has seen the passage of centuries, and let’s not forget the quiet rivers that snake through the country, their banks decorated with bright colors of Ukrainian flora, but the charm of Ukraine extends not only to its physical beauty, but also to its culture, steeped in tradition and history, as well as fascinating as its landscape. This is a country where folk tales come to life.
Keywords: туризм український; Ukrainian tourism